2015
DOI: 10.1371/journal.ppat.1005054
|View full text |Cite
|
Sign up to set email alerts
|

Vpr Promotes Macrophage-Dependent HIV-1 Infection of CD4+ T Lymphocytes

Abstract: Vpr is a conserved primate lentiviral protein that promotes infection of T lymphocytes in vivo by an unknown mechanism. Here we demonstrate that Vpr and its cellular co-factor, DCAF1, are necessary for efficient cell-to-cell spread of HIV-1 from macrophages to CD4+ T lymphocytes when there is inadequate cell-free virus to support direct T lymphocyte infection. Remarkably, Vpr functioned to counteract a macrophage-specific intrinsic antiviral pathway that targeted Env-containing virions to LAMP1+ lysosomal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 50 publications
(88 reference statements)
3
33
2
Order By: Relevance
“…Previous work in this field suggests that Vpr likely regulates a complex network of host interactions that may vary depending on the cell type infected. We find that, unlike what has been previously observed in activated CD4 ϩ T cells and monocyte-derived macrophages (20,(22)(23)(24)(25)29), infection of MDDCs with ΔVpr viruses was significantly attenuated compared to WT HIV-1 infections (Fig. 1), similar to the findings reported previously by de Silva et al (41).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous work in this field suggests that Vpr likely regulates a complex network of host interactions that may vary depending on the cell type infected. We find that, unlike what has been previously observed in activated CD4 ϩ T cells and monocyte-derived macrophages (20,(22)(23)(24)(25)29), infection of MDDCs with ΔVpr viruses was significantly attenuated compared to WT HIV-1 infections (Fig. 1), similar to the findings reported previously by de Silva et al (41).…”
Section: Discussionsupporting
confidence: 89%
“…Although a number of previous studies have examined the requirement of Vpr for HIV-1 replication in various cell types, including primary CD4 ϩ T cells and monocytederived macrophages (MDMs), differences in virus replication have not been consistently observed (18,20,(22)(23)(24)(25)(26). Vpr expression is dispensable for infection in activated CD4 ϩ T cells in vitro (22)(23)(24)(25)27), presumably due to the well-characterized cytostatic and cytopathic functions of Vpr in cycling cells (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently suggested that Vpr favors infection of macrophages by counteracting a restriction factor targeting Env expression and viral release (12). Vpr is also necessary for efficient cell-to-cell spread of HIV-1 from macrophages to CD4 + T lymphocytes (13). Vpr plays an important role in vivo.…”
mentioning
confidence: 99%
“…It was recently suggested that Vpr favors infection of macrophages by counteracting a restriction factor targeting Env expression and viral release (33). Vpr is also necessary for efficient cell-to-cell spread of HIV-1 from macrophages to CD4 ϩ T lymphocytes (34). Vpr plays an important role in vivo.…”
mentioning
confidence: 99%